Analysis of Household Consumer Demand Against Sea Fresh Fish In North Padangsidimpuan District Padangsidimpuan City North Sumatra Province - Rosmalayuni Rambe; Eni Yulinda; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from April 29th until May 6th 2013 in theDistrict of North Padangsidimpuan Padangsidimpuan City of North SumatraProvince. The purpose of the research was to describe and analyze thecharacteristics of consumer demand for fresh fish as well as determine how themagnitude of the factors that influence household consumer demand for fresh fishin the North Padangsidimpuan District.Basically the level of consumer demand for a product is determined byseveral factors. On fresh fish products, the factors that affect the price of freshfish such as itself, the price of substitutes (chicken meat), income, dependents, andconsumer taste. The results showed that the dominant gender consumers arewomen with ages ranging from 41-50 years, the majority of formal education ishigh school, and her work as a housewife. Based grouping of income, the majorityof consumers belonged to the upper middle class. Consumer demand for fresh fishis influenced by economic and non-economic factors. The most influential factoris the price of chicken meat was 2.068 (highly significant), whereas the otherfactors do not affect the demand significant fresh sea fish.Keywords : Demand Analysis, household consumers, Fresh sea fish